The role of impulsivity and emotional dysregulation in smartphone overdependence explored through network analysis - Jinwoo Cho; Hoyoung Kim (Scientific Reports)
Abstract Smartphone overdependence is a maladaptive behavior characterized by excessive and uncontrollable smartphone use despite negative consequences. Impulsivity and emotional dysregulation, which are multidimensional constructs with each factor exerting a different effect, have been found to influence the development and persistence of smartphone overdependence. This study utilized network analysis to investigate the intricate relationships between the factors of impulsivity, emotional dysregulation, and smartphone overdependence. A sample of 687 adults in their twenties completed an online survey. Central nodes of the network were “Impulse-control difficulties,” “Positive Urgency,” “Salience” and “Relapse,” and bridge nodes included a “Lack of emotional awareness and understanding,” “Negative Urgency,” “Lack of Perseverance,” and “Impulse-control difficulties.” These findings suggest that emotion-related impulsivity plays a pivotal role in smartphone overdependence and emotional dysregulation, with impulsivity acting as a critical mediator between emotional dysregulation and smartphone overdependence.